THE RELATIONSHIP BETWEEN STRESS LEVELS AND THE QUALITY OF LIFE OF NURSES AT MITRA MEDIKA TANJUNG MULIA HOSPITAL MEDAN IN 2025 - Afina Muharani Syaftriani; Maya Ardilla Siregar; Hizrah Hanim Lubis; Dedi; Siti Aisyah; Andika Herlina Marda Prawata (RADJA PUBLIKA, 2025)
Occupational stress is a common problem experienced by nurses due to high job demands, heavy workloads, and responsibility for patient safety. Poorly managed stress can negatively impact nurses' physical and psychological health, ultimately affecting their quality of life. Therefore, research is needed to determine the relationship between stress levels and the quality of life of nurses in hospitals. The purpose of this study was to determine the relationship between stress levels and the quality of life of nurses at Mitra Medika Tanjung Mulia Hospital, Medan, in 2025. This study used a quantitative design with a correlational approach and cross-sectional methods. The study population was all 175 nurses working at Mitra Medika Tanjung Mulia Hospital, Medan, with a sample size of 64 respondents determined using the Slovin formula and quota sampling techniques. Data collection was conducted using a stress questionnaire and the WHOQOL-BREF questionnaire to measure quality of life. Data analysis included univariate and bivariate analyzes using the chi-square test with a significance level of α = 0.05. The results showed that the majority of respondents experienced mild and moderate stress (31 respondents (48.4%), respectively), and the majority of nurses (40 respondents (62.5%) reported a good quality of life. Bivariate levels analysis revealed a significant relationship between stress and nurses' quality of life. Medika Tanjung Mulia Hospital, Medan.